Water quality of Samsam peat swamp based on physical-chemical parameters Kandis Sub-District, Siak District, Raiu Province - Sihotang, Clemens; Simarmata, Asmika Harnalin; ', Edduardo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Samsam swamp is located in the peat soil area and flooded during rainy season. To understand the water quality of the swamp, a research has been conducted from Maret-April 2016. There were four sampling sites, namely S1 is in the upstream (almost no human activity); S2 (around palm plantation), S3 (around the newly planted palm plantation) and S4 (far from palm plantation). Water samples were taken once/week for a 3 weeks period.Water quality parameters measured were depths, temperature, transparency, pH, DO, CO2, nitrate and phosphate. Results shown that depths was 39-170 cm, temperature: 28-32 oC, pH : 4-5, DO :3.96-4.93 mg/L, CO2: 4-11,99 mg/L, nitrate : 0.33-0.63 mg/L, and phosphate 0.37-0.65 mg/L. Nitrate concentration indicate that the Samsam peat swamp was categorized as mesotrophic-eutrophic, and phosphate concentration indicate that the Samsam peat swamp is hypertrophic.Keywords : Samsam peat swamp, Water Quality, oligotrophic-mesotrophic,hypertrophic.